Effect of the Android-Based e-LabVir Application on Learning Independence and Science Learning Effectiveness of Generation Z Students in Dynamic Electricity Material - Nova Elysia Ntobuo; Lanto Mohamad Kamil Amali; Lanto Ningrayati Amali; Citron Payu; I Made Hermanto; Lukman Samatowa; Doung Ratha (Jurnal Pendidikan Sains Indonesia, 2025)
In an ideal school, laboratories are an integral part. However, not all schools in Indonesia have adequate laboratories, or even laboratory space. One alternative is to utilize virtual laboratories. Utilization of virtual laboratories is a viable and efficacious approach for practicum implementation, offering a potential solution to the constraints associated with laboratory equipment. However, the majority of virtual laboratories are not compatible with android devices due to the size of the data required to download the necessary applications. Furthermore, there is a paucity of android-based virtual laboratories, and even those that exist often require internet data during operation. In light of the aforementioned considerations, the objective of this research is to develop an android-based virtual laboratory learning media. This research employs the ADDIE development method to create an android-based virtual laboratory that utilizes minimal internet data, with the majority of data being used only during the installation process. Once the application is installed, the virtual laboratory can be utilized without requiring an internet connection. The findings indicated that the virtual laboratory met the standards of validity as determined by expert evaluation. Moreover, preliminary trials conducted with 24 students at SMP Negeri 2 Gorontalo revealed that 83% of students provided highly positive feedback, while 17% offered positive responses. Additionally, the findings indicated that students exhibited commendable autonomy in their learning process when utilizing an android-based virtual laboratory